Development of Competency-Based Curriculum to Prepare Students for Global Challenges - Harianto, Jakoep Ezra (Asian Journal of Multidisciplinary Research, 2024)
The development of a competency-based curriculum is one of the important efforts in preparing students to face global challenges in the modern era. This article aims to examine the importance of curriculum development that prioritizes strengthening student competencies in order to respond to the dynamics of global change. This study uses a qualitative method with a library research approach to analyze various relevant reference sources related to competency-based curriculum development. Based on the results of the literature study, it was found that the competency-focused curriculum not only emphasizes academic knowledge, but also practical skills that can be applied in various global contexts, such as critical thinking skills, creativity, adaptability, and problem-solving. In addition, this research also highlights the importance of technology integration in learning and collaboration between countries in developing a curriculum that is relevant to global developments. The results of this study provide recommendations for the development of a curriculum that is more flexible, based on industry needs, and able to prepare students for the challenges of an increasingly competitive world of work. In conclusion, the development of a competency-based curriculum is a strategic step to ensure the readiness of future generations to face the ever-evolving global challenges.